48. Clinical Characteristics of Acute Flaccid Myelitis Cases Associated with Enteroviruses D68 and A71 — United States, 2018. (31st December 2020) - Kidd, Sarah; Lopez, Adriana; Nix, W Allan; Anyalechi, Gloria E; Itoh, Megumi; Yee, Eileen L; Oberste, M Steven; Routh, Janell A
Abstract: Background: Acute flaccid myelitis (AFM) is an uncommon but serious condition that causes paralysis in previously healthy children. Multiple viruses can be associated with AFM. In 2018, enteroviruses D68 (EV-D68) and A71 (EV-A71) were the most common viruses detected among patients with confirmed AFM. We described and compared clinical characteristics of cases associated with EV-D68 and EV-A71. Methods: Health departments report cases meeting AFM clinical criterion (acute onset of flaccid limb weakness) to the Centers for Disease Control and Prevention along with medical records. Confirmed AFM cases were patients who met clinical criterion and had magnetic resonance imaging (MRI) showing spinal cord lesions largely restricted to gray matter. We abstracted clinical data and laboratory results from records of confirmed case-patients with onset of limb weakness during 2018. EV-D68 and EV-A71 cases were compared using chi-square and Wilcoxan rank sum tests. Results: Among 238 confirmed AFM cases, 34 had EV-D68 and 12 had EV-A71 detected in a respiratory, serum, stool, or cerebrospinal fluid specimen. Median age of EV-D68 and EV-A71 cases were 5.9 and 1.6 years, respectively (p< 0.01). EV-D68 cases came from 20 states, while 11/12 EV-A71 cases were from Colorado. Prodromal respiratory illness was more common among EV-D68 (97%) than EV-A71 cases (58%) (p< 0.01). Prodromal rash was more common among EV-A71 (58%) than EV-D68 cases (9%) (p< 0.01). At presentation, the most common symptoms accompanying limb weakness among EV-D68 cases were neck/back pain (59%), gait difficulty (56%), and fever (47%). Among EV-A71 cases, the most common symptoms were fever (67%), ataxia (67%), gait difficulty (50%), and altered consciousness (50%). EV-A71 cases were more likely to have ataxia, altered consciousness, and brainstem (92% vs. 45%) or cerebellar (75% vs. 9%) lesions on MRI (all p< 0.01). EV-D68 cases were more likely to require mechanical ventilation (44% vs. 8%, p 0.03). Conclusion: These national data suggest that EV-D68 and EV-A71 are associated with overlapping but different clinical phenotypes. Differences in demographics, prodromal illness, symptoms, and brain MRI findings were identified. Additional research is needed to determine whether pathogenesis and optimal treatment also vary by virus type. Disclosures: All Authors : No reported disclosures